A study of the factors influencing students' achievement of business Chinese in Nanyang Technological University - Lim, Adeline Ai Lin (2014)
In view of the increasing interest in Business Mandarin, the project attempts to examine the impact of Socio-economic, Socio-cultural, Attitudinal and Motivational factors in the students' achievement of Business Chinese in Nanyang Technological University.